TRIM37 exacerbates hepatic ischemia/reperfusion injury by facilitating IKKγ translocation - Hang Yang; Zuotian Huang; Yunhai Luo; Dengliang Lei; Ping Yan; Ai Shen; Wenbin Liu; Dewei Li; Zhongjun Wu (Molecular Medicine, 2023)
Abstract Background Hepatic ischemia/reperfusion (I/R) injury is one of the major pathological processes associated with various liver surgeries. However, there is still a lack of strategies to protect against hepatic I/R injury because of the unknown underlying mechanism. The present study aimed to identify a potential strategy and provide a fundamental experimental basis for treating hepatic I/R injury. Method A classic 70% ischemia/reperfusion injury was established. Immunoprecipitation was used to identify direct interactions between proteins. The expression of proteins from different subcellular localizations was detected by Western blotting. Cell translocation was directly observed by immunofluorescence. HE, TUNEL and ELISA were performed for function tests. Result We report that tripartite motif containing 37 (TRIM37) aggravates hepatic I/R injury through the reinforcement of IKK-induced inflammation following dual patterns. Mechanistically, TRIM37 directly interacts with tumor necrosis factor receptor-associated factor 6 (TRAF6), inducing K63 ubiquitination and eventually leading to the phosphorylation of IKKβ. TRIM37 enhances the translocation of IKKγ, a regulatory subunit of the IKK complex, from the nucleus to the cytoplasm, thereby stabilizing the cytoplasmic IKK complex and prolonging the duration of inflammation. Inhibition of IKK rescued the function of TRIM37 in vivo and in vitro. Conclusion Collectively, the present study discloses some potential function of TRIM37 in hepatic I/R injury. Targeting TRIM37 might be potential for treatment against hepatic I/R injury.Targeting TRIM37 might be a potential treatment strategy against hepatic I/R injury. Graphical Abstract